2006
DOI: 10.1097/01.aids.0000218555.36661.9c
|View full text |Cite
|
Sign up to set email alerts
|

HIV incidence and factors associated with HIV acquisition among injection drug users in St Petersburg, Russia

Abstract: The high incidence of HIV infection places St Petersburg among the worst IDU-concentrated epidemics in Europe. Interventions targeting psychostimulant and heroin users and their accompanying behaviors such as frequent injections and increased sexual activity are needed immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
1
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 9 publications
5
88
1
4
Order By: Relevance
“…13 Our finding that IDUs practicing higher injection-related risk behavior are more likely to be practicing higher sexual risk behavior is consistent with other research findings. [14][15][16][17][18][19] There is some evidence from other studies in line with our results that those injecting buprenorphine might have lower HIV-related risky injection practices.…”
Section: Discussionsupporting
confidence: 92%
“…13 Our finding that IDUs practicing higher injection-related risk behavior are more likely to be practicing higher sexual risk behavior is consistent with other research findings. [14][15][16][17][18][19] There is some evidence from other studies in line with our results that those injecting buprenorphine might have lower HIV-related risky injection practices.…”
Section: Discussionsupporting
confidence: 92%
“…Social and economic factors (including high youth unemployment, a boom in drug trafficking, and the growth of informal economies) associated with the disintegration of the former Soviet Union have fuelled rampant injecting drug use in the Russian Federation (Rhodes et al, 2006). A study in St Petersburg, for example, has found that almost two thirds (62%) of drug users are un-or underemployed (Kozlov et al, 2006).…”
Section: E a S T E R N E U R O P E A N D C E N T R A L A S Imentioning
confidence: 99%
“…Up to two thirds of the injecting drug users testing HIV-positive in such studies were unaware that they had been infected (Rhodes et al, 2006). More recently, in St Petersburg, HIV incidence of 5% was found among injecting drug users, the majority of whom (79%) reported using non-sterile equipment (Kozlov et al, 2006). In some cities of Russia, more harm reduction projects are now in operation, but they are too few in number and too small in scale to significantly affect overall HIV trends.…”
Section: E a S T E R N E U R O P E A N D C E N T R A L A S Imentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, among HIV infected women who have never injected drugs, almost half have had sex with an IDU [5]. HIV prevalence and incidence rates among IDU in St. Petersburg have been consistently high, with a 30% prevalence and an incidence of 4.5 per 100 person-years in 2003 [6,7], 14 per 100 person-years incidence in 2008 [8], and 35% prevalence and 7.2 per 100 person-years incidence in 2010 [9].…”
Section: Introductionmentioning
confidence: 99%